1996
DOI: 10.1007/bf02053811
|View full text |Cite
|
Sign up to set email alerts
|

Transanal endoscopic microsurgery

Abstract: TEM has a low complication rate. By carefully selecting small, superficial cancers and adenomas, TEM results in superior outcome over other approaches to the mid and upper rectum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 11 publications
6
68
1
3
Order By: Relevance
“…Other studies have also demonstrated good results with low recurrence and high survival for selected pT1N0 rectal adenocarcinomas treated by TEM alone 2,4,8,13,20,21,36 . In the advent that pathological examination reveals a pT1 lesion with unfavorable features or a more advanced lesion the authors recommend complementary treatment with radical surgery and/or CMT.…”
Section: Early Rectal Cancersmentioning
confidence: 89%
“…Other studies have also demonstrated good results with low recurrence and high survival for selected pT1N0 rectal adenocarcinomas treated by TEM alone 2,4,8,13,20,21,36 . In the advent that pathological examination reveals a pT1 lesion with unfavorable features or a more advanced lesion the authors recommend complementary treatment with radical surgery and/or CMT.…”
Section: Early Rectal Cancersmentioning
confidence: 89%
“…The latter include inadvertent entry into the peritoneal cavity during fullthickness excision of high rectal lesions located above the peritoneal reflection [17] . While this occurrence was originally considered a major complication of TEM and was managed by conversion to laparotomy in an effort to prevent intraabdominal infection [18] , a study comparing the morbidity associated with fullthickness excision with and without peritoneal entry in 34 TEM fullthickness excisions demonstrated that in all 11 cases where the peritoneal cavity was inad vertently entered and subsequently closed, no infectious complications were noted [19] . In addition, no significant differences in the complication rates were noted between the groups with or without peritoneal entry [19] .…”
Section: Advantages Of Transcolonic/ Transanal Notes Accessmentioning
confidence: 99%
“…Recurrence of rectal polyps has been reported to be 4-13 %, and redo-TEM remains an option in such recurrences. TEM is increasingly being used for the excision of lesions in patients who are poor surgical candidate [8][9][10].…”
Section: Introductionmentioning
confidence: 99%